2022
DOI: 10.3390/curroncol29090507
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current and Emerging Therapies for Advanced Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma remains a leading cause of cancer-related deaths worldwide. Liver disease including cirrhosis and viral hepatitis remains among the leading causes of hepatocellular carcinoma and despite increased screening, many patients are diagnosed in the advanced stages precluding them from locoregional therapy. Therapeutic agents for advanced hepatocellular carcinoma were limited to Sorafenib for several years; however, with the emergence of molecular targeted therapies including tyrosine kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Sorafenib is currently a first‐line chemotherapeutic drug for treatment of advanced HCC and metastatic colon cancer. 35 However, oral administration of sorafenib is associated with a variety of adverse effects, including diarrhea and fatigue, which can lead to discontinuation of chemotherapy and cardiovascular events, including hypertension. 36 More importantly, patients frequently develop multidrug resistance (MDR) shortly after sorafenib exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is currently a first‐line chemotherapeutic drug for treatment of advanced HCC and metastatic colon cancer. 35 However, oral administration of sorafenib is associated with a variety of adverse effects, including diarrhea and fatigue, which can lead to discontinuation of chemotherapy and cardiovascular events, including hypertension. 36 More importantly, patients frequently develop multidrug resistance (MDR) shortly after sorafenib exposure.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is a global health concern, with the incidence reaching >90,000 cases by 2025 [ 25 , 26 ]. ICD is a modality that is closely associated with tumorigenesis development by recognizing surface antigens that further induce immune cell collections on tumor cells, thereby promoting necrosis through immune cell infiltration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy is typically reserved for tumours with large vascular invasion, those that can no longer be controlled with local therapy approaches or those with extrahepatic metastases. Unlike ICC, cytotoxic chemotherapy has had little benefit and systemic treatment is either a variety of tyrosine kinase inhibitors (TKIs) such as sorafenib or lenvatinib, or IO agents in combination with targeted therapy 21 22. First-line systemic therapy preferred regimens are either the combination of atezolizumab and bevacizumab per the IMBrave 150 study23 or tremelimumab plus durvalumab, after the results of the HIMALAYA trial demonstrated improved OS when compared with sorafenib 24…”
Section: Introductionmentioning
confidence: 99%